(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to the study of the influence of modern means of communication on the development of the Russian language in non-Russian-speaking institutions. The phenomena observed in the speech of Internet users are considered in the context of two opposing and interrelated trends - towards formalization and deformalization of communication.